The Effect of the EDJA Model on Attentional Control and Learning the Skills of Serve Reception and Blocking in Volleyball among Second-Year Students in the Department of Physical Education and Sport Sciences (Journal of the College of Basic Education, 2026)
The aim of the research was to design educational exercises and employ them using the EDGA model, and to identify the effect of educational exercises based on the EDGA model on attentional control and on learning the performance of the skills of serve reception and blocking in volleyball among students. The researcher adopted the experimental method using a design with two groups (experimental and control). The sample consisted of 56 students, who were intentionally selected, representing 63.636% of their population, which comprised second-year students in the Department of Physical Education and Sport Sciences, College of Education, Al-Farahidi University, for the academic year (2025–2026). After preparing the attentional control scale and the two skill tests, the educational exercises based on the EDGA model were implemented at a rate of one instructional unit per week for eight consecutive weeks. Each skill was taught through four instructional units to the students of the experimental group. After completing the experiment, the data were processed using the SPSS statistical system. The results concluded that employing educational exercises based on the EDGA model in volleyball instructional units is appropriate for second-year students in the Department of Physical Education, College of Education, Al-Farahidi University. The application of these exercises also contributed to improving the level of attentional control and enhancing the performance of the serve reception and blocking skills in volleyball among the students who learned through this model, outperforming their peers who learned without it. Accordingly, the researcher recommended the necessity of paying attention to measuring attentional control for each student during practical lessons to support the improvement of their skill performance when learning volleyball skills using the EDGA model. It is also necessary to give importance to the type of ideas and cognitive inputs presented to students during the teaching of volleyball skills through the EDGA model.